PENGARUH KOMBINASI BIOSLURRY DAN AIR KOTORAN LELE TERHADAP TANAMAN JAGUNG (Zea mays L.) - I Made Sudiarta; Ady Prabowo; Sarintan Gubali; Aprianus Buheli; Zulham Sirajuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The purpose of this study was to identify the effect of different mixtures of bioslurry and catfish manure on the growth and production of hybrid maize. This research was conducted on the experimental field of the Technical Implementation Unit (UPT) of Agricultural Innovation, Universitas Ichsan Gorontalo, for 4 months from February to May 2022, which was conducted to examine the best formula for a mixture of organic fertilizer made from bioslurry and catfish wastewater manure through experiments. The field experiment design was arranged based on a Randomized Block Design (RAK) which consisted of 5 treatments and 3 replications, resulting with 15 experimental plots. The results of this study showed that the combination of treatment of bioslurry with catfish wastewater manure had a significant effect on the variable length of corn cobs in treatment B1 (75% bioslurry combined with catfish wastewater 25%), and was the best treatment for the variable number of leaves, cob length, cob diameter, wet shelled weight and dry shelled weight of corn.